Preliminary Development of Solid Dispersion for an Insoluble Compound ZL006 by Miniaturized Hot Melt Extrusion - Zhang, Lijun; Luan, Hansen; Lu, Weiyue; Wang, Hao (Pharmaceutical Fronts, 2019)
The purpose of this study was to develop a solid dispersion (SD) by miniaturized hot-melt extrusion (HME) for an insoluble molecule ZL006 which showed potency of increasing leukocytes. A preliminary formulation screening was conducted using solvent evaporation method. The selected SD formulation was further optimized and scaled up using a miniaturized twin-screw extruder. Solid-state characterizations of the scale-up SD and its corresponding physical mixture (PM) were performed by X-ray powder diffraction (XRPD), modulated differential scanning calorimetry (mDSC), and Fourier's transform infrared spectroscopy (FTIR). XRPD and mDSC results indicated the formation of amorphous SD. FTIR spectrum indicated the possible hydrogen bond formation between the compound and the excipient. A discriminating non-sink condition micro-dissolution of SD showed the fast release of ZL006 which was approximately two-fold and three-fold of dissolution of PM and pure crystalline compound, respectively. The preliminary in vivo pharmacokinetics (PK) study in rats showed 71% oral bioavailability from the SD, while the bioavailability of ZL006 conventional suspension was less than 1%. Thus, an SD formulation for ZL006 with improved solubility and bioavailability was developed by miniaturized HME with minimal amount of compound at early preclinical stage, which could enable the preclinical evaluation.
Keywords: solid dispersion; hot-melt extrusion; miniaturized; Soluplus; hydroxypropyl methylcellulose acetate succinate; ZL006